Biologically engineered microbes for bioremediation of electronic waste: Wayposts, challenges and future directions. Issue 1 (26th February 2022) - Han, Ping; Teo, Wei Zhe; Yew, Wen Shan
Abstract: In the face of a burgeoning stream of e‐waste globally, e‐waste recycling becomes increasingly imperative, not only to mitigate the environmental and health risks it poses but also as an urban mining strategy for resource recovery of precious metals, rare Earth elements, and even plastics. As part of the continual efforts to develop greener alternatives to conventional approaches of e‐waste recycling, biologically assisted degradation of e‐waste offers a promising recourse by capitalising on certain microorganisms' innate ability to interact with metals or degrade plastics. By harnessing emerging genetic tools in synthetic biology, the evolution of novel or enhanced capabilities needed to advance bioremediation and resource recovery could be potentially accelerated by improving enzyme catalytic abilities, modifying substrate specificities, and increasing toxicity tolerance. Yet, the management of e‐waste presents formidable challenges due to its massive volume, high component complexity, and associated toxicity. Several limitations will need to be addressed before nascent laboratory‐scale achievements in bioremediation can be translated to viable industrial applications. Nonetheless, vested groups, involving both start‐up and established companies, have taken visionary steps towards deploying microbes for commercial implementation in e‐waste recycling.